2014
DOI: 10.5633/amm.2014.0403
|View full text |Cite
|
Sign up to set email alerts
|

Essential Arterial Hypertension and Risk Factors Associated With Hypertensive Nephropathy

Abstract: Arterial hypertension is a major risk factor that predisposes to cardiovascular disorders and is responsible for most of the morbidity and mortality in patients. Hypertension is closely associated with the kidney, because kidney disease can be both the cause and consequence of increased blood pressure. Elevation of blood pressure is a strong independent risk factor for hypertensive nephropathy and development of ESRD. The pathogenesis of ischemic hypertensive nephropathy (IHN) is multifactoral, and in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…19 The estimated GFR according to the MDRD equation was in a significant inversely proportional relationship with duration and stages of arterial hypertension, and the same relationship was found between eCrCl CGBMI1.73 and eGFR CGBMI1.73 and the duration and stage of arterial hypertension. 19 Research has shown that the habit of smoking is still a large problem for patients in Bosnia and Herzegovina, and preventive programs aiming to reduce progression of atherosclerotic disease should be part of the daily work of medical doctors in primary health care. bubrežne bolesti pokazano je kod bolesnika sa šećernom bolesti i AH ako su rabljeni ACE inhibitori ili ARB.…”
Section: Raspravamentioning
confidence: 57%
See 3 more Smart Citations
“…19 The estimated GFR according to the MDRD equation was in a significant inversely proportional relationship with duration and stages of arterial hypertension, and the same relationship was found between eCrCl CGBMI1.73 and eGFR CGBMI1.73 and the duration and stage of arterial hypertension. 19 Research has shown that the habit of smoking is still a large problem for patients in Bosnia and Herzegovina, and preventive programs aiming to reduce progression of atherosclerotic disease should be part of the daily work of medical doctors in primary health care. bubrežne bolesti pokazano je kod bolesnika sa šećernom bolesti i AH ako su rabljeni ACE inhibitori ili ARB.…”
Section: Raspravamentioning
confidence: 57%
“…Milojkovic et al investigated the correlation between essential arterial hypertension and hypertensive nephropathy among 283 subjects as well as the prevalence of risk factors for the development of atherosclerotic changes. 19 A significant correlation was found between a positive anamnesis, arterial hypertension, smoking, and dyslipidemia in relation to the prevalence of hypertensive nephropathy. 19 The estimated GFR according to the MDRD equation was in a significant inversely proportional relationship with duration and stages of arterial hypertension, and the same relationship was found between eCrCl CGBMI1.73 and eGFR CGBMI1.73 and the duration and stage of arterial hypertension.…”
Section: Raspravamentioning
confidence: 94%
See 2 more Smart Citations
“…
В настоящее время артериальную гипер-тензию (АГ) рассматривают в качестве основ-ного фактора риска сердечно-сосудистых забо-леваний, а также как наиболее частую причину временной нетрудоспособности, причиняющей работодателям значительные убытки [11, 14,17]. Известно, что АГ -мультифакториальное забо-левание, имеющее генетическую предрасполо-женность.
…”
unclassified